Multicolour photochromic fluorescence of a fluorophore encapsulated in a metal–organic framework. Issue 67 (21st July 2020) - Hirai, Kenji; Kitagawa, Taisei; Fujiwara, Hideki; Pirillo, Jenny; Hijikata, Yuh; Inose, Tomoko; Uji-i, Hiroshi
Abstract : A fluorophore encapsulated in a metal–organic framework showed photochromic multicolour fluorescence. Abstract : A fluorophore encapsulated in a metal–organic framework showed photochromic multicolour fluorescence. Irradiation with an ultraviolet laser induced the relocation of the fluorophore from a polar to a nonpolar environment, altering the emission from red to blue. This change in emission color can be repeatably recovered by heating the fluorophore–MOF composite.